Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV Sekolah Dasar - Pusung, Supit; Pati, Lucia A. M. (Peneliti.net, 2023)
The aim of this research is to improve science learning outcomes through the application of the problem based learning (PBL) model for fourth grade students at SD GMIM V Tomohon. The research method used is classroom action research carried out in two cycles, the procedures in each cycle are: planning, implementation, observation and reflection. From the results of the existing research and discussion, researchers can conclude that the learning outcomes of respiratory organs in humans using the Problem Based Learning (PBL) model in cycle I, the percentage of completeness of student learning outcomes was 50% with an average score of 68.93 and increased in the cycle II with a student completion percentage of 100% with an average score of 87.86. Based on the results at SD GMIM 5 Tomohon, it can be concluded that the application of the Problem Based Learning (PBL) model can improve learning outcomes in science subjects regarding human respiratory organs in class IV of SD GMIM V Tomohotion